Autologous/reduced-intensity allogeneic stem cell transplantation vs autologous transplantation in multiple myeloma: long-term results of the EBMT-NMAM2000 study - Gahrton, Gösta; Iacobelli, Simona; Björkstrand, Bo; Hegenbart, Ute; Gruber, Astrid; Greinix, Hildegard; Volin, Liisa; Narni, Franco; Carella, Angelo M.; Beksac, Meral; Bosi, Alberto; Milone, Giuseppe; et al. (Blood, 2013)
Long-term follow-up of prospective studies comparing allogeneic transplantation to autologous transplantation in multiple myeloma is few and controversial. This is an update at a median follow-up of 96 months of the European Group for Blood and Marrow Transplantation Non-Myeloablative Allogeneic stem cell transplantation in Multiple Myeloma (NMAM)2000 study that prospectively compares tandem autologous/reduced intensity conditioning allogeneic transplantation (auto/RICallo) to autologous transplantation alone (auto). There are 357 myeloma patients up to age 69 years enrolled. Patients with an HLA-identical sibling were allocated to auto/RICallo (n = 108) and those without to auto alone (n = 249). At 96 months progression-free survival (PFS) and overall survival (OS) were 22% and 49% vs 12% (P = .027) and 36% (P = .030) with auto/RICallo and auto respectively. The corresponding relapse/progression rate (RL) was 60% vs 82% (P = .0002). Non-relapse mortality at 36 months was 13% vs 3% (P = .0004). In patients with the del(13) abnormality corresponding PFS and OS were 21% and 47% vs 5% (P = .026), and 31% (P = .154). Long-term outcome in patients with multiple myeloma was better with auto/RICallo as compared with auto only and the auto/RICallo approach seemed to overcome the poor prognostic impact of del(13) observed after autologous transplantation. Follow up longer than 5 years is necessary for correct interpretation of the value of auto/RICallo in multiple myeloma.